Designing Incentives to Change Behaviors: Examining College Student Intent Toward Healthy Diets. (September 2016) - McComb, Sara; Jones, Carmen; Smith, Alison; Collins, William; Pope, Brandon
College is a time when young adults establish lifestyle habits. This research examines how personalization and limited resources might be balanced most effectively when designing incentives to shift college students' intentions toward positive dietary changes. A randomized 2 × 2 experiment (Coaching/Coupons × Fruits and Vegetables/Low Fat) was conducted, where respondents were exposed to virtual interventions and asked pre- and post-intervention about their intent to eat healthy. Results suggest that interventions may incentivize students, but are dependent on student characteristics. On-campus students and students with more knowledge about healthy diets were more likely to increase their intent when offered coaching; students living off campus and those with less knowledge resonated with coupons. On- and off-campus students differed in their positive responses to eating fruits and vegetables versus low fat foods, respectively. Younger students may be more susceptible to interventions. Findings may be useful in designing meaningful incentives for college students.